The status and evolution of energy supply and use in Mexico prior to the 2014 energy reform: An input-output approach - Zeus Guevara; Oscar Córdoba; Edith X. M. García; Rafael Bouchain (Economies, 2017)
In 2014, the Mexican government approved a bold energy reform that allows private energy companies to freely participate in the energy market (something prohibited during the previous eight decades). This reform is expected to significantly restructure the energy sector and boost and diversify the energy production. Moreover, changes in the energy sector and production might lead to structural changes in the rest of the economy and ultimately generate significant economic benefits for the country. Nevertheless, the fundamental role of the energy sector in this oil producing country makes the potential impacts of the reform complex to forecast. The objective of the study is to analyze the current state, evolution, and driving factors of the total primary energy use in Mexico in 2003-2012 (prior to the implementation of the reform) as a precedent for future analyses of impacts of the energy reform. The results show three driving factors of the evolution of primary energy use: final non-energy demand, direct energy intensity, and economic structure. Also, it was found that the energy sector has been in a precarious situation regarding its structure and efficiency. However, this situation had a small effect on the evolution of primary energy use.
Keywords: Q43; O13; 330; energy-economic transition; Mexican energy reform; energy input-output analysis